1992
DOI: 10.1103/physrevd.46.474
|View full text |Cite
|
Sign up to set email alerts
|

Soft charge form factor of the pion

Abstract: We identify the source of a discrepancy between pPft /long and FP'~~~,,,, found by Isgur and Llewellyn Smith. We find that the discrepancy disappears when virtual qq pair production for longitudinal-momentum transfers is included. Our result rectifies the discussion by Isgur and Llewellyn Smith of soft nonperturbative effects at presently available values of Q2. PACS Number(s): 13.40.Fn, ll.lO.St, 1 2 . 3 8 . B~ While perturbative Q C D ( P Q C D ) [l-51 is expected t o be a n adequate tool t o study the asymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 32 publications
3
53
0
Order By: Relevance
“…An example is the Drell-Yan overlap formula [13] of the elastic form factor, for which Isgur and Llewellyn Smith [7] observed that different results are obtained in different reference frames. Sawicki [18] has shown the origin of this discrepancy: in certain reference frames there are overlap contributions which are not contained in the Drell-Yan formula; when they are taken into account Lorentz invariance is restored. We shall first review Sawicki's arguments [18,19] for the form factor and then investigate the case of Compton scattering.…”
Section: Bethe-salpeter and Light Cone Wave Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An example is the Drell-Yan overlap formula [13] of the elastic form factor, for which Isgur and Llewellyn Smith [7] observed that different results are obtained in different reference frames. Sawicki [18] has shown the origin of this discrepancy: in certain reference frames there are overlap contributions which are not contained in the Drell-Yan formula; when they are taken into account Lorentz invariance is restored. We shall first review Sawicki's arguments [18,19] for the form factor and then investigate the case of Compton scattering.…”
Section: Bethe-salpeter and Light Cone Wave Functionsmentioning
confidence: 99%
“…Sawicki [18] has shown the origin of this discrepancy: in certain reference frames there are overlap contributions which are not contained in the Drell-Yan formula; when they are taken into account Lorentz invariance is restored. We shall first review Sawicki's arguments [18,19] for the form factor and then investigate the case of Compton scattering.…”
Section: Bethe-salpeter and Light Cone Wave Functionsmentioning
confidence: 99%
“…Other choice of q µ will cause contribution from Z-graphs, and it should give the same result as that in the q + = 0 case if all graphs are taken into account [26]. Therefore some more complicated diagrams should be included.…”
Section: Pion-photon and Photon-pion Transition Form Factorsmentioning
confidence: 99%
“…It is worth noting that in the timelike region the full result for the pion form factor is always given by the pair-production process (''Z-diagram'') alone, independently of this approximation, while in the spacelike region only the ''Z-diagram'' contribution [14,19,21,22,27,41] survives for a massless pion [26]. The importance of the ''Z-diagram'' contribution to the electromagnetic current for q > 0 was also recently investigated in the context of the Bethe-Salpeter equation within the light-front quantization in Ref.…”
mentioning
confidence: 99%